2003
DOI: 10.1152/ajpheart.00137.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of burst stimulation during ventricular fibrillation on cardiac function after defibrillation

Abstract: The purpose of defibrillation is to rapidly restore blood flow and tissue perfusion following ventricular fibrillation (VF) and shock delivery. We tested the hypotheses that 1) a series of 1-ms pulses of various amplitudes delivered before the defibrillation shock can improve hemodynamics following the shock, and 2) this hemodynamic improvement is due to stimulation of cardiac or thoracic sympathetic nerves. Ten anesthetized pigs received a burst of either 15 or 30 1-ms pulses (0.1–10 A in strength) during VF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…Shock-induced Ca i 2+ changes were implicated in the inotropic effect of low-energy shocks applied during defibrillation and alleviation of after-shock "pulse-less electrical activity" [7,8,21]. The results of the present study do not support this hypothesis.…”
Section: Mechanisms Of Shock-induced δCa I 2+contrasting
confidence: 89%
See 2 more Smart Citations
“…Shock-induced Ca i 2+ changes were implicated in the inotropic effect of low-energy shocks applied during defibrillation and alleviation of after-shock "pulse-less electrical activity" [7,8,21]. The results of the present study do not support this hypothesis.…”
Section: Mechanisms Of Shock-induced δCa I 2+contrasting
confidence: 89%
“…Effects of shocks on Ca i 2+ are considered important for understanding post-shock arrhythmias and changes in cardiac contractility [6][7][8]. Previously, shock-induced Ca i 2+ changes were measured in cell cultures and analyzed in an ionic model during the early AP phase [9].…”
Section: Mechanisms Of Shock-induced δCa I 2+mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we showed that burst stimulation delivered during short duration VF just before the shock improved hemodynamics following defibrillation 7. Further, beta-adrenergic blockade prior to electrical stimulation blocked the hemodynamic improvement, showing that the electrical burst was stimulating the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 81%
“…Previously we have shown that delivering a series of 1-ms pulses during short duration (10–20 s) ventricular fibrillation, stimulates the autonomic nervous system to increase myocardial function following defibrillation 7. Further, we have shown that myocardial catecholamine levels are at near toxic levels after defibrillation and reperfusion following several minutes of ventricular fibrillation 8.…”
Section: Introductionmentioning
confidence: 97%